ANALYSIS OF THE PHYSICAL COMPONENTS OF THE ABILITY TO DRIBBLE THE SOCCER GAME FOR STUDENTS OF SMP NEGERI 1 SINJAI REGENCY - Andi Ihsan; Ahmad Adil (Hanoman Journal: Physical Education and Sport, 2023)
This study aims to determine how big the contribution or the relationship between physical components and the ability to dribble in football games. This research is a descriptive study with two variables, namely, the physical Condition (X) and the ability to dribble (Y). The population of this research is the students of SMP Negeri 1 Kabupaten Sinjai. By random sampling, a sample of 40 students was selected. The data collection technique used a physical component measurement test including agility, speed and balance with the ability to dribble. The data analysis technique used is correlation analysis using computer facilities through the SPSS program. Based on the data analysis, the results showed that there was a significant contribution or relationship between the physical components and the ability to dribble, the value of r arithmetic (R) = 0.439 (P 0.05) and a contribution of 19.3%.